2015
DOI: 10.1109/tnsre.2014.2371391
|View full text |Cite
|
Sign up to set email alerts
|

Using Actual and Imagined Walking Related Desynchronization Features in a BCI

Abstract: Recently, brain-computer interface (BCI) research has extended to investigate its possible use in motor rehabilitation. Most of these investigations have focused on the upper body. Only few studies consider gait because of the difficulty of recording EEG during gross movements. However, for stroke patients the rehabilitation of gait is of crucial importance. Therefore, this study investigates if a BCI can be based on walking related desynchronization features. Furthermore, the influence of complexity of the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
4
18
0
1
Order By: Relevance
“…These results demonstrated that the alpha and beta bands were equivalently involving in the walking in terms of inter-regional connectivity. The equivalent contribution to the walking was roughly in agreement with the observation that power spectral densities (PSD) of these two bands were concurrently changed relevant to walking [11], [28], [10] as well as the movements of upper limbs [45]. This might be due to that the alpha and beta bands are modulated to accomplish the largely overlapping part of the motor function.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results demonstrated that the alpha and beta bands were equivalently involving in the walking in terms of inter-regional connectivity. The equivalent contribution to the walking was roughly in agreement with the observation that power spectral densities (PSD) of these two bands were concurrently changed relevant to walking [11], [28], [10] as well as the movements of upper limbs [45]. This might be due to that the alpha and beta bands are modulated to accomplish the largely overlapping part of the motor function.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the neural mechanism of contra-lateral control from the brain to upper limbs, lower limbs are controlled by contralateral brain hemispheres although the regions controlling respective lower limbs are closer to the midline of the brain [9]. According to the previous investigations, we have known that power spectral densities (PSD) extracted from the EEG recordings under different walking conditions were different [10], [11], [12], hemispherical asymmetry in the PSD was differential between the walking condition with an exoskeleton and the walking condition without an exoskeleton [13], the PSD was suppressed during walking compared to the upright standing [14], and the correlative relationship between brain activity and muscular contraction of the lower limb [15] and so forth. These differences among walking conditions have been utilized as features, based on which different walking conditions were successfully classified [10], [16], [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, multiple studies have been conducted focused on the development of this type of rehabilitation systems [18][19][20]. In this regard, brain-machine interfaces (BMIs) can lead to a significant improvement in rehabilitation systems for patients who have suffered a stroke, making them an active part of their own rehabilitation process and thus achieving not only a rehabilitation at muscle level but also an improvement at neurological level, since it is the patients themselves who generate the control commands of the system [21].…”
Section: Thesis Motivationmentioning
confidence: 99%
“…(2) Event-Related Synchronizations or Desynchronizations (ERS/ERD). Studies have shown that the single side of the body movement or imaginary movement can generate ERD in contralateral brain and ERS in ipsilateral brain [3]. (3) Slow Cortical Potential (SCP).…”
Section: Introductionmentioning
confidence: 99%